Epigenetic memory of cell fate commitment - Elsherbiny, Adel; Dobreva, Gergana (Current opinion in cell biology, 2021)
During development, discrete cell fates are established in precise spatiotemporal order guided by morphogen signals. These signals converge in the nucleus to induce transcriptional and epigenetic programming that determines cell fate. Once cell identity is established, cell programs have to be accurately sustained through multiple rounds of cell division, during which DNA replication serves as a window of opportunity for altering cell fate. In this review, we summarize recent advances in understanding the molecular players that underlie epigenetic memory of cell fate decisions, with a particular focus on histone modifications and mitotic bookmarking factors. We also discuss the different mechanisms of inheritance of repressed and active chromatin states.
Gesehen am 14.07.2021
Available online 31 January 2021